1999
DOI: 10.1177/019262339902700115
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Evaluation of rhuMAbVEGF, an Antiangiogenic Humanized Monoclonal Antibody

Abstract: Recombinant humanized antivascular endothelial growth factor (rhuMAbVEGF) is a monoclonal IgG1 antibody that is being developed as an antiangiogenic agent for use in treating a variety of solid tumors. Preclinical safety studies included an immunohistochemical tissue cross-reactivity study, in vitro hemolytic potential and blood compatibility studies, and multiple dose toxicity studies. Toxicity studies were conducted in cynomolgus monkey because rhuMAbVEGF is pharmacologically active in this species and does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(87 citation statements)
references
References 71 publications
3
82
1
1
Order By: Relevance
“…This is the first study to report the effects of a VEGF receptor kinase inhibitor on follicular development, although a soluble VEGF receptor construct has been previously found to have inhibitory effects on corpora luteal angiogenesis and development in mice (55) and a KDR blocking antibody shown to significantly delay follicular development in rhesus monkey (56). Analogous changes in bone growth plate and ovary have also been observed in primate following treatment with the VEGF-neutralizing antibody, bevacizumab (57). AZD2171 (1.5 and 6 mg per kg per day) completely abolished VEGF-dependent angiogenesis in vivo, in a s.c. Matrigel plug assay, suggesting that it might also inhibit tumor growth at comparatively small doses.…”
Section: Discussionmentioning
confidence: 92%
“…This is the first study to report the effects of a VEGF receptor kinase inhibitor on follicular development, although a soluble VEGF receptor construct has been previously found to have inhibitory effects on corpora luteal angiogenesis and development in mice (55) and a KDR blocking antibody shown to significantly delay follicular development in rhesus monkey (56). Analogous changes in bone growth plate and ovary have also been observed in primate following treatment with the VEGF-neutralizing antibody, bevacizumab (57). AZD2171 (1.5 and 6 mg per kg per day) completely abolished VEGF-dependent angiogenesis in vivo, in a s.c. Matrigel plug assay, suggesting that it might also inhibit tumor growth at comparatively small doses.…”
Section: Discussionmentioning
confidence: 92%
“…(Tammela et al, 2005;Ferrara and Gerber, 2001;Carmeliet and Collen, 2000;Yancopoulos et al, 2000;Rossant and Howard, 2002). Although VEGF is a critical regulator in physiological angiogenesis it also plays a significant role in skeletal growth (Zelzer et al, 2002;Gerber et al, 1999;Haigh et al, 2000;Ryan et al, 1999) and repair (Street et al, 2002;Chu et al, 2002;Peng et al, 2002).…”
Section: Osteogenesis Angiogenesis and Bone Tissue Engineeringmentioning
confidence: 99%
“…In the bone remodelling sequence Niida et al, (1999) showed VEGF can act with sRANKL to promote osteoclastogenesis and that a single injection of recombinant human VEGF can similarly induce osteoclast recruitment in op/op mice, suggesting that VEGF can act as a substitute for M-CSF in osteoclastogenesis. Street and colleagues (Street et al, 2000;Street et al, 2002;Ryan et al, 1999;Gerber et al, 1999) have demonstrated that the inhibition of VEGF in fractured mouse femurs results in a decrease in blood vessel invasion with a reduction in osteoclastic bone remodelling, impaired callus mineralization and reduced trabecular bone healing.…”
Section: Angiogenesis and Bone Fracture Repairmentioning
confidence: 99%
“…7 Postnatal VEGF blockade results in stunted growth, increased mortality due to renal failure, and impaired organ development, 8,9 while experimental blockade in juvenile primates causes ovarian failure and stunted growth due to chondrocyte failure within the epiphyseal growth plates. 10 In adults, VEGF infusion stimulates microvascular perfusion in patients with severe coronary artery disease and ischemic limbs. 11,12 Although new blood vessel growth in response to ischemic myocardium may be lifesaving, 13 pathologic neovascularization and hyperpermeability in other organs, such as the eye, cause blindness from retinal detachment, uncontrollable glaucoma, and untreatable retinal edema.…”
mentioning
confidence: 99%